2017
DOI: 10.1051/0004-6361/201732182
|View full text |Cite
|
Sign up to set email alerts
|

Thermal conductivity of porous aggregates

Abstract: Context. The thermal conductivity of highly porous dust aggregates is a key parameter for many subjects in planetary science; it is not yet fully understood, however. Aims. We investigate the thermal conductivity of fluffy dust aggregates with filling factors lower than 10 −1 . Methods. We determined the temperature structure and heat flux of the porous dust aggregates calculated through N-body simulations of static compression in the periodic boundary condition. Results. We derive an empirical formula for the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 34 publications
(49 reference statements)
4
25
0
Order By: Relevance
“…We perform three-dimensional numerical calculations of dust aggregates using the model described by Arakawa et al (2017). Here we briefly summarize our numerical methods.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We perform three-dimensional numerical calculations of dust aggregates using the model described by Arakawa et al (2017). Here we briefly summarize our numerical methods.…”
Section: Methodsmentioning
confidence: 99%
“…For highly porous aggregates, however, Z(φ) is approximately two and behaves as a constant, hence f (φ) would only depend on φ for highly porous aggregates. Arakawa et al (2017) revealed that f (φ) is approximately proportional to the square of φ for highly porous aggregates with filling factors below 10 −1 . In this study, we calculate the dimensionless function of the thermal conductivity f (φ) for both loose (i.e., Z 2) and close (i.e., Z > 2) dust aggregates.…”
Section: Thermal Conductivitymentioning
confidence: 99%
See 1 more Smart Citation
“…In our computations, the heat conduction coefficient is assumed to be κ = 0.00025 W/m/K, which corresponds to a realistic value for a porous dust aggregate (Krause et al 2011;Arakawa et al 2017;Sakatani et al 2017 coefficient depends on porosity, grain size, and composition. Increasing the heat conduction coefficient flattens the superheating phase functions.…”
Section: Application To the Coma Of 67pmentioning
confidence: 99%
“…(D.4) Therefore, F Ph /F D is independent of a for the case of a < l m , while F Ph /F D is inversely proportional to the square of the particle radius for the case of a > l m This means that the radial drift of cm-sized compact pebbles could not be prevented by photophoresis itself, although the radial drift would be stopped because the pressure maximum formed at the light barrier. We note, however, that the thermal conductivity of dust aggregates is exceedingly lower than that of compact dust particles (e.g., Arakawa et al 2017Arakawa et al , 2019, and the radial drift of aggregated pebbles might be stopped by photophoresis, even if their radius is larger than the mean free path of the gas molecules. Temperature T [K] p = 10 0 dyn cm -2 p = 10 2 dyn cm -2 p = 10 4 dyn cm -2 p = 10 6 dyn cm -2 fitting 10 -5 10 -4 10 -3 10 -2 10 -1 10 0 10 1 10 2 10 2 10 3 where c p = 10 7 erg g −1 K −1 is the specific heat (e.g., Ciesla et al 2004).…”
Section: Appendix D: Mean Free Path Of Gas Moleculesmentioning
confidence: 72%